Handbook of contemporary paganism - Lewis, James R.; Pizza, Murphy. (Brill Handbooks on Contemporary Religion, 2009)
Contemporary Paganism is a movement that is still young and establishing its identity and place on the global religious landscape. The members of the movement are simultaneously growing, unifying, and maintaining its characteristic diversity of traditions, identities, and rituals. The modern Pagan movement has had a restless formation period but has also been the catalyst for some of the most innovative religious expressions, praxis, theologies, and communities. As Contemporary Paganism continues to grow and mature, new angles of inquiry about it have emerged and are explored in this collection. This examination and study of contemporary Paganism contributes new ways to observe and examine other religions, where innovations, paradoxes, and inconsistencies can be more accurately documented and explained.